Pengaruh Perputaran Kas, Persediaan, Piutang, Modal Kerja Terhadap Profitabilitas Perusahaan - Siti Dini; Silvia Silalahi; Elverida Marpaung; Dewi S. Sihombing; Lestari Rajagukguk (Jurnal Ekonomi, 2020)
The purpose of this study is to determine the effect of Cash Turnover, Inventory Turnover, Receivable Turnover, and Working Capital Turnover on Profitability in Consumers Manufacturing Industry Manufacturing Companies Listed on the Indonesia Stock Exchange in 2015-2017. The research method used a quantitative approach, the type of descriptive research and its cumulative causal nature. The research population was 50 companies and the sample was 14 companies with a purposive sampling technique. Data collection techniques by means of documentation and sources of IDX financial statements. This study uses a multiple linear regression test before testing the data hypothesis and is tested using the classic assumption test. The results of the analysis of the coefficient of determination obtained R Square value of 0.152, which means the variance of the profitability variable that can be explained by the variables Cash Turnover, Inventory Turnover, Receivable Turnover, and Working Capital Turnover is 15.2% and the remaining 84.8% is explained by other variables. This research shows that simultaneous cash turnover, inventory turnover, accounts receivable turnover, and working capital turnover has a positive and significant effect on profitability. Partially Cash Turnover has no effect on Profitability, Inventory Turnover has a negative and no significant effect on Profitability, Accounts Receivable Turnover has no effect on Profitability and Working Capital Turnoverpositive and significant effect on Profitability.